2009
DOI: 10.1021/jf901682m
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surfactant Properties on Oxidative Stability of β-Carotene Encapsulated within Solid Lipid Nanoparticles

Abstract: The impact of surfactant type on the physical and chemical stability of solid lipid nanoparticle (SLN) suspensions containing encapsulated beta-carotene was investigated. Oil-in-water emulsions were formed by homogenizing 10% w/w lipid phase (1 mg/g beta-carotene in carrier lipid) and 90% w/w aqueous phase (surfactant + cosurfactant) at pH 7 and 75 degrees C and then cooling to 20 degrees C. The impact of surfactant type was investigated using aqueous phases containing different water-soluble surfactants [2.4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
2
6

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(112 citation statements)
references
References 42 publications
3
101
2
6
Order By: Relevance
“…The problem was that these regions were most likely the dispersing phase for β-carotene, oxidative agents and any dissolved oxygen. Another reason for the low capacity of preservation of the β-carotene in the solid lipid particles of HPKO could have been the location of the carotenoid in the structure, as it might have been forced to migrate to the surface of the particles due to the formation of lipid crystals (Okuda et al 2005;Helgason et al 2009;Cornacchia and Roos 2011b). The location at the surface would facilitate the contact with prooxidant species present in the aqueous phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem was that these regions were most likely the dispersing phase for β-carotene, oxidative agents and any dissolved oxygen. Another reason for the low capacity of preservation of the β-carotene in the solid lipid particles of HPKO could have been the location of the carotenoid in the structure, as it might have been forced to migrate to the surface of the particles due to the formation of lipid crystals (Okuda et al 2005;Helgason et al 2009;Cornacchia and Roos 2011b). The location at the surface would facilitate the contact with prooxidant species present in the aqueous phase.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid-based matrices are known to improve the bioavailability of hydrophobic bioactives, which make these matrices especially interesting as encapsulation systems. Recent advances have shown that one of the approaches to improve the solubility and bioavailability of poorly soluble substances, such as carotenes and tocopherols, is to incorporate these compounds in lipid-based encapsulation systems (Helgason et al 2008, Helgason et al 2009Nik et al 2011;Shukat and Relkin 2011;Wang et al 2012). Several structured lipid-based delivery systems are available to encapsulate, protect and deliver the hydrophobic bioactive compounds in the form of lipid droplets (emulsions, microemulsions, nanoemulsions, multiple emulsions), liposomes, coated particles (multilayer emulsions, colloidosomes) and solid lipid particles (McClements 2010;McClements and Li 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Among the lipid-based carriers that can be used in food, there are the solid lipid particles, which have structures similar to those of oil-in-water emulsions, where the oily core is replaced by a solid lipid at room temperature (Müller et al, 2000). Solid lipid particles are used to encapsulate and protect sensitive lipophilic compounds and present different advantages, such as low toxicity, possibility of controlling the release of the encapsulated compounds, low cost, and application of biocompatible and biodegradable solid lipids (Helgason et al, 2009;Mehnert & Mader, 2001). The encapsulation of beta-carotene in this type of lipid-based carrier has been already studied in the literature, with promising results (Gomes et al, 2013a, b;Cornacchia & Characterization and evaluation of sensory acceptability of ice creams incorporated with beta-carotene encapsulated in solid lipid microparticles Roos, 2011;Hentschel et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As partículas lipídicas sólidas, tanto micro quanto nanopartículas, são sistemas carreadores que têm sido desenvolvidos para encapsular, proteger e liberar componentes funcionais lipofílicos, tais como bioativos lipídicos e drogas hidrofóbicas. Os lipídios utilizados são sólidos à temperatura ambiente e corpórea, além de serem biológicos e biodegradáveis o que a princípio indica baixa toxicidade do sistema (FREITAS & MULLER, 1998;HEURTAULT et al, 2003;HELGASON et al, 2009;PARHI & SURESH, 2010). Essa característica, juntamente com seu tamanho normalmente submicrométrico, e potencial para produção em escala industrial, têm proporcionado um interesse muito grande, nos últimos anos, por tais sistemas (RUKTANONCHA et al, 2009).…”
Section: Partículas Lipídicas Sólidasunclassified
“…No entanto, infelizmente a biodisponibilidade de muitos carotenóides, especialmente quando em sua forma cristalina, é muito baixa, e a sua estabilidade oxidativa diminui muito durante o processamento devido à mistura de produtos químicos e exposição ao calor (HENTSCHEL et al, 2008;HELGASON et al 2009 …”
Section: Carotenóides: Estrutura E Microencapsulaçãounclassified